How do you solve this equation for x?
(1/2)(x + 18) = 4(2x − 6) − 9x
(1/2)(x + 18) = 4(2x − 6) − 9x
(1/2)(x + 18) = 8x  24  9x {used the distributive property on the right side} (1/2)(x + 18) = x  24 {combined like terms on the right side} x + 18 = 2x  48 {multiplied the entire equation by 2 to eliminate the fraction} 3x = 66 {added 2x and subtracted 18 from each side} x = 22 {divided each side by 3} Ask Algebra House
0 Comments
Your comment will be posted after it is approved.
Leave a Reply. 
Archives
February 2023
